Optical And Humidity Sensing Properties Of Pure Zno And Zno/Sno2Thin Films Deposited By Spray Paralysis Method (International Journal of Scientific Research and Management (IJSRM), 2015)
The present study, we have synthesized ZnO/SnO2 thin films prepared by spray paralysis method and characterized by UV-visible transmission and photoluminescence (PL) spectroscopy and humidity sensing. In UV-visible spectroscopy thin film found to be transparent and its transmission is 20% - 85%. In visible and infrared region with sharp cut off at 310 nm. In PL study shows UV emission which shift to lower wavelength as SnO2 is introduced. The ratio of 1:5 in ZnO:SnO2, shows maximum PL intensity. The PL intensity is found to decrease with increase the ratio of SnO2 in ZnO. The highest intensity peak centered at 375 to 415 nm which show the violet emission. The presence of different broad peak shows the presence of defect states during synthesis and fabrication of the thin films. The humidity sensing of ZnO:SnO2 thin films shows very low values of response and recovery time indicating potential candidature. Response and recovery time of samples is very low which shows suitability of prepared samples for humidity sensors.